Stress intensity factors for multiple cracks in thick-walled cylinder - G. Girase, Krunal; Patil, Navneet K.; Shinde, Dinesh; Kalita, Kanak (International Journal of Scientific World, 2015)
The stress intensity factor (SIF) is the linear elastic fracture mechanics parameter that relates remote load, crack size and structural geometry. It predicts very accurately the stress state. In this work, cylinders with multiple cracks are considered. The following parameters are varied during the analysis of the cylinders: the number of cracks, (the variation in number of cracks ultimately led to a variation in the inter-crack spacing), the crack length to cylinder thickness ratio (a/t), the diameter ratio of the cylinders. Very good agreement between the finite element stresses and the theoretical stresses is seen.